Unintended Lessons of Revolution : Student Teachers and Political Radicalism in Twentieth-Century Mexico. - Padilla, Tanalís. (Durham : Duke University Press, 2022)
Tanalís Padilla traces the history of the normales rurales--rural schools in Mexico that trained campesino teachers--and outlines how despite being intended to foster a modern, patriotic citizenry, they became sites of radical politics.
Cover -- Contents -- Acknowledgments -- List of abbreviations -- Introduction: Ayotzinapa and the Legacy of Revolution -- 1. Normales, Education, and National Projects -- 2. A New Kind of School, a New Kind of Teacher -- 3. "And That's When the Main Blow Came" -- 4. Education at a Crossroads -- 5. "The Infinite Injustice Committed against Our Class Brothers" -- 6. Learning in the Barricades -- 7. "A Crisis of Authority," -- 8. "That's How We'd Meet . . . Clandestinely with the Lights Off" -- Epilogue: Education, Neoliberalism, and Violence -- Appendix: Sample Rural Normal Class Schedules -- Notes -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- X -- Y -- Z.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books